Illegal fishing as a trans-national organized crime - Nilam Andalia Kurniasari, Dina Sunyowati, Lina Hastuti Enny Narwati, (Opción, 2019)
This article aims to investigate illegal fishing as a trans-national organized crime and is written based on empirical-qualitative research conducting through observation, conduct interviews with law enforcement officials and government agencies. As a result, the biggest challenges in combating illegal fishing include several aspects such as politics, law, institutions, educations, and law enforcement. In conclusion, eliminating Illegal, Unregulated, and Unreported (IUU) Fishing requires bilateral, regional, and international cooperation and it needs common perception among States to categorize IUU Fishing as TOC so that criminal justice system can be implemented effectively.